Polymer-based 3D printed millimeter-wave components for spacecraft payloads - Lucyszyn,S; Shang,X; Otter,W; Myant,C; Cheng,R; Ridler,N (IEEE MTT-S, 2018)
This paper summarizes the current state of research & development within the U.K. for polymer-based 3D printed guided-wave and quasi-optical components for spacecraft payloads. Preliminary measured results look promising and show that this emerging technology may well overtake existing machined technologies in the not too distant future for general aerospace applications.